The Relationship Between Financial Condition and Business Cycle in Mongolia - Gan-Ochir Doojav; Munkhbayar Purevdorj (East Asian Economic Review (EAER), 2019)
This paper examines the interactions between financial conditions and business cycles in Mongolia, a small open economy, heavily depending on commodity exports. We construct two financial conditions indexes based on the reduced form IS model and the vector autoregression (VAR) model as surveillance tools to quantify the degree of the financial conditions. We find that real short-term interest rate and real effective exchange rate gap get a higher weight in the FCIs. Both business and financial cycles are often more pronounced in Mongolia, and financial condition is dependent of the financial and monetary policies in place. The analysis of the predictive power of the FCIs for business cycles shows that they have predictive information for the near-term economic activities. FCIs are also helpful in signaling inflation turning points.
Keywords: C32; E17; E44; 330; Financial Condition Index; Business Cycle; Leading Indicator; Weighted Sum Approach; Mongolia